Temporal Stability of Heavy Drinking Days and Drinking Reductions Among Heavy Drinkers in the COMBINE Study. (5th April 2017) - Witkiewitz, Katie; Wilson, Adam D.; Pearson, Matthew R.; Hallgren, Kevin A.; Falk, Daniel E.; Litten, Raye Z.; Kranzler, Henry R.; Mann, Karl F.; Hasin, Deborah S.; O'Malley, Stephanie S.; Anton, Raymond F.
Abstract : Background: Recently, the Food and Drug Administration (FDA) proposed to expand the options for primary end points in the development of medications for alcohol use disorder to include either abstinence from alcohol or a nonabstinent outcome: no heavy drinking days (with a heavy drinking day defined as more than 3 drinks per day for women and more than 4 drinks per day for men [>3/>4 cutoff]). The FDA also suggested that 6 months would be the most appropriate length for a clinical trial to demonstrate the stability of this nonabstinent drinking outcome. However, few alcohol clinical trials have examined the stability of nonheavy drinking during and after treatment. Methods: In a secondary analysis of the COMBINE study data ( n = 1, 383), we examined transitions in heavy drinking days during the course of treatment (months 1 through 4), during the transition out of treatment (months 4 through 7), and up to 12 months afterward (months 13 through 16) using latent variable mixture models. Results: Heavy drinking and nonheavy drinking were relatively stable in consecutive months (minimum agreement [kappa] = 0.64 for months 1 to 2). Most individuals were stable low‐risk drinkers/abstainers or heavy drinkers by the end of treatment, as characterized by a 10% probability (or less) of transitioning out of either a no heavy drinking state or a heavy drinking state. More than two‐thirds of the heavy drinkers who exceeded the heavy drinking threshold during treatment reported, on average, a 64% reduction in drinking frequency and a 38% reduction in drinking intensity from pretreatment drinking levels. Conclusions: The results show stability of no heavy drinking as an outcome within the first 4 months of treatment and that the >3/>4 drink cutoff may mask substantial reductions in alcohol consumption among some patients. Future studies should explore the clinical utility of reduction end points. Abstract : Results from this study show stability of no heavy drinking as an outcome within the early months of treatment and that the heavy drinking cutoff, defined as more than three drinks for women and four drinks for men, may mask substantial reductions in alcohol consumption among some patients. More than two‐thirds of those who exceeded the heavy drinking threshold during treatment reported, on average, a 64% reduction in drinking frequency and 38% reduction in drinking intensity from pretreatment levels.